Effects of different degrees of drought stress on plants and flowering physiology in Satsuma mandarin (Citrus unshiu ‘Yura’) - HUANG Bei; WANG Peng; WEN Mingxia; WU Shaohui; XU Jianguo (浙江大学学报. 农业与生命科学版, 2021)
In order to study the responses of Satsuma mandarin ‘Yura’ plants to different drought treatments and the relative expression levels of flowering related gene FLOWERING LOCUS T (FT) and meristem related gene APETALA1 (AP1), two-year-old Satsuma mandarin plants were treated with various degrees of limited water, including well watering (CK), light drought (LD), moderate drought (MD) and severe drought (SD), whose soil moisture were 15%-20%, 12%-15%, 8%-10%, and 4%-6%, respectively, and kept for 20, 30, and 40 d, respectively. After treatments, the plant physiology, flowering physiology and relative expression levels of flowering related genes FT and AP1 were tracked. The results indicated that the treatment of MD for 30 d affected the plant growth slightly and the physiological and morphological differentiations of flower buds were earlier than those of other treatment groups. The relative expression level of FT reached peak under the treatment of MD for 30 d, and the relative expression levels of AP1 in stems and leaves were higher at 30 d after MD treatment. In general, moderate drought for 30 d is the suitable inducement condition of flower bud’s morphological differentiation in Satsuma mandarin, and will not cause serious damage to trees. Also the effect of early flowering has also been further verified at the gene transcription level.